Productivity of alley and sole cropping of berseem (Trifolium alexandrinum)- sorghum (Sorghum bicolor) and forage bushes under different moisture regimes in hot sub-humid region of central India - Dhar, Shiva; Shukla, N P; Burman, D (The Indian Journal of Agricultural Sciences, 2005)
A study was conducted during 1996-99 in a hot sub-humid region of central India to assess forage-based cropping systems with and without hedgerows at different moisture regimes. The 5 cropping systems [berseem (Trifolium alexandrinum L.)-sorghum [Sorghum bicolor(L.) Moench], Sesbania sesban (L.) Merr. as sole crop, Leucaena leucocephala (Lam.) de Wit as sole crop, berseem-sorghum with Sesbania and berseem-sorghum with Leucaena hedgerows] were assessed under 3 moisture regimes (irrigation at 0.5,0.75 and 1.0 irrigation water (60 mm depth)/cumulative pan evaporation ratio). The green biomass (187 tonnes/ha), dry matter (32 tonnes/ha) and crude protein (4.75 tonnes/ha) yields were significantly higher in a berseem-sorghum alley crop sequence with Leucaetla hedgerows followed by the same alley crop sequence with Sesbania hedgerows. The berseem-sorghum alley sequence with Leucaena hedgerows provided green fodder for a longer duration including lean periods. The Sesbania species was found more sensitive to pruning and higher mortality was recorded in Sesbania. Irrigation at 0.5 to 0.75 irrigation water (60 mm depth)/cumulative pan evaporation ratio significantly increased the green biomass, dry matter and crude protein yields. Further increases did not increase the yields significantly. The water use efficiency decreased with increasing soil moisture. Green biomass yield during third growing season was higher (230 tonnes/ha) in the berseem-sorghum crop sequence alley with Leucaena hedgerows irrigated at 1.0 IW/CPE ratio. The annual soil moisture depletion was higher (172.1 cm) in this cropping system.